2009
DOI: 10.3233/ch-2009-1212
|View full text |Cite
|
Sign up to set email alerts
|

Extra- and intracellular signaling pathways under red blood cell aggregation and deformability changes

Abstract: Exposure of red blood cells (RBCs) to catecholamines (epinephrine, phenylephrine, an agonist of α 1 -adrenergic receptors, clonidine, an agonist of α 2 -adrenergic receptors and isoproterenol, an agonist of β-adrenergic receptors) led to change in the RBC microrheological properties. When forskolin (10 µM), an AC stimulator was added to RBC suspension, the RBC deformability (RBCD) was increased by 17% (p < 0.05). Somewhat more significant deformability rise appeared after RBC incubation with dB-AMP (by 27%; p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…It is conceivable that the shear force applied during the CS procedure may directly affect the deformability as well as the shape of RBCs (15,16). The erythrocyte deformability affects the HV (17,18). In our study, although we observed that HV tended to increase after the procedure in these three groups, only Group F yielded statistical significance.…”
Section: Discussioncontrasting
confidence: 60%
“…It is conceivable that the shear force applied during the CS procedure may directly affect the deformability as well as the shape of RBCs (15,16). The erythrocyte deformability affects the HV (17,18). In our study, although we observed that HV tended to increase after the procedure in these three groups, only Group F yielded statistical significance.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, drugs that inhibit the phosphodiesterase enzyme (PDE) like pentoxifylline improve blood viscosity via amelioration of erythrocyte deformability; thus vinpocetine reduced the erythrocytes aggregations through cGMP-dependent pathway leading to the improvement in erythrocyte deformability [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of the SNS on cancer cell mechanotype remain to be investigated, activation of β‐adrenoceptor signaling is known to regulate the mechanical properties of other cell types, including blood and muscle cells. Treating red blood cells and airway smooth muscle cells with the β‐adrenoceptor agonist, isoproterenol, makes these cells more deformable 34 , 35 . In contrast, treating primary cardiomyocytes with the same drug makes these cells stiffer 36 .…”
Section: Neural Signaling Regulates Tumor Cell Structure and Metastasismentioning
confidence: 99%